Authentication and identification markers for medicinal plants: I Aristolochia bracteolata - Khandhar, Dharam B.; Bhatt, Pritesh P.; Thaker, Vrinda S. (International Journal of Scientific Reports, 2021)
Background: Aristolochiaceae is a unique plant family that contains aristolochic acids (AAs), with around 600 species. Methods: The entire chloroplast genome of Aristolochia bracteolata was sequenced in this work, and fourteen chloroplast (cp) genomes were retrieved from the NCBI database. Results: We also analyzed six types of microsatellite markers among these species and found some different markers for each species. A molecular phylogeny based on 7 barcode regions i.e. matK, atpF to atpH, psbK to psbI, rbcL, rpoB, rpoC2 and rpoC1 is proposed for Aristolochia and 16 species from Piperales, Arabidopsis thaliana is taken as an outgroup. Phylogenetic relationships using concatenated protein-coding genes from Chloroplast genomes of Piperales using the maximum likelihood method is also discussed. Conclusions: In the present study we are providing some unique markers and phylogenetic relationships among Piperales members which will help in identification, authentication, to prevent adulteration and further investigation of these medicinal plants.